"I Don't Feel Like Myself": Treating Frailty in the Elderly With Diet. Issue 6 (November 2016) - Firnhaber, Gina C.; Kolasa, Kathryn M.
Abstract : Attention to the role diet and nutrition play in frailty may help older adults better perform basic activities of daily living, have a better quality of life, and delay disability. While there are no well-accepted guidelines for the prevention and treatment of frailty, providing patients with strategies for improving their diets may help them prevent, delay, reduce, or reverse prefrailty and frailty. In this article, we present the case of an older adult who might benefit from frailty assessment and dietary counseling.